The Therapeutic Potency of HSP65-GTL in GL261 Glioma-bearing Mice. Issue 9 (November 2015) - Yan, Youyou; Fang, Mingli; Xuan, Wei; Wu, Xiuli; Meng, Xiuping; Wang, Liying; Yu, Yongli
Abstract : Gliomas are the most common type of brain tumor with poor prognosis. Even after combination treatments including surgery, radiation, and chemotherapy, the median survival is around 15 months, calling for novel approaches such as immunotherapy. To develop novel therapeutic approaches, we tried to prepare a candidate vaccine by mixing the recombinant mycobacterial heat-shock protein 65 (HSP65) with GL261 glioma tissue lysate (GTL). Our data showed that HSP65-GTL induced potent cytotoxic T lymphocyte and prolonged the survival of mice bearing GL261 gliomas. Furthermore, HSP65 or HSP65-GTL upregulated mRNA expressions of RORγt and interleukin-17A in spleen cells or draining lymph node cells, respectively, and enhanced the ratios of brain-infiltrating Th17 cells and inflammatory cells, indicating that the antitumor effect of HSP65-GTL was associated with Th17-type immunity.